Sulfate attack performance of concrete mixtures with use of copper slag as supplementary cementitious material - Yimmy Fernando Silva; Claudia Burbano-Garcia; Gerardo Araya-Letelier; Silvia Izquierdo (Case Studies in Construction Materials)
One of the most significant causes of concrete structural degradation is sulfate attack, stemming from the interaction between hydration products of cement and sulfate ions, which causes physical and microstructural changes in the material matrix that can severely affect concrete’s mechanical performance. This study evaluates the short and long term (up to 360 days) sulfate resistance performance of concretes incorporating copper slag (CS), a major global mining waste, as supplementary cementitious material (SCM). Three concrete mixtures with increasing CS replacement levels (i.e., 0 %, 20 % and 50 % by volume replacement of ordinary Portland cement) were exposed to aggressive sulfate environment, specifically sodium sulfate (Na2SO4) and magnesium sulfate (MgSO4) solutions, each containing 33,800 ppm of SO4–2. A comprehensive analysis of physical (linear expansion and visual inspection), mechanical (compressive strength and modulus of elasticity) and mineralogical (scanning electron microscopy (SEM) and X-ray diffraction (XRD)) properties was conducted. The results indicated that physical changes were most significant in the mixtures exposed to MgSO4 compared to those exposed to Na2SO4. Additionally, higher compressive strength losses at 360 days were observed, with reductions of 18 %, 21 % and 15 % for the mixtures with 0 %, 20 % and 50 % of CS as SCM, respectively. The elastic modulus results showed a similar trend to compressive strength, with the 20 % CS mixture exhibiting comparable stiffness to the reference, while the 50 % CS mixture showed a noticeable reduction. In mineralogical terms, characteristic crystals such as ettringite and gypsum were identified in all exposed concretes by XRD and SEM. Finally, these findings demonstrate that incorporating CS as an SCM does not adversely affect the sulfate resistance of concrete mixtures and supports its potential use in durable, sustainable concrete applications.